2009
DOI: 10.1038/ncb1847
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation by Akt1 promotes cytoplasmic localization of Skp2 and impairs APCCdh1-mediated Skp2 destruction

Abstract: Deregulated Skp2 function promotes cell transformation, and this is consistent with observations of Skp2 over-expression in many human cancers. However, the mechanisms underlying elevated Skp2 expression remain elusive. Here we report that the serine/threonine protein kinase Akt1, but not Akt2, directly controls Skp2 stability by a mechanism that involves degradation by the APC/Cdh1 ubiquitin ligase complex. We further show that Akt1 phosphorylates Skp2 at Ser72, which is required to disrupt the interaction be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
239
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 227 publications
(261 citation statements)
references
References 49 publications
19
239
3
Order By: Relevance
“…Consistently, we did not observe significant changes in the mRNA levels of Cdh1 ( Figure 3A) or the APC Cdh1 substrates Cdc20 ( Figure 3B) and Skp2 ( Figure 3C) in Fbw7 −/− DLD1 cells compared with the WT DLD1 cells. On the other hand, using either Cycloheximide [41,42] or Anisomycin [43] to block protein synthesis as a means to measure protein stability, we Figure S3A, and S3D-S3H). These results indicate that increased protein stability, but not changes in mRNA levels, contributes to the elevated expression of various APC Cdh1 substrates in Fbw7 −/− cells.…”
Section: Fbw7 Regulates the Stability Of Various Apc Cdh1 Substratesmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistently, we did not observe significant changes in the mRNA levels of Cdh1 ( Figure 3A) or the APC Cdh1 substrates Cdc20 ( Figure 3B) and Skp2 ( Figure 3C) in Fbw7 −/− DLD1 cells compared with the WT DLD1 cells. On the other hand, using either Cycloheximide [41,42] or Anisomycin [43] to block protein synthesis as a means to measure protein stability, we Figure S3A, and S3D-S3H). These results indicate that increased protein stability, but not changes in mRNA levels, contributes to the elevated expression of various APC Cdh1 substrates in Fbw7 −/− cells.…”
Section: Fbw7 Regulates the Stability Of Various Apc Cdh1 Substratesmentioning
confidence: 99%
“…Cell culture and cell synchronization experiments were performed as previously described [41,50]. Lentiviral shRNA packaging and infection were also performed as previously described [51].…”
Section: Cell Culture and Cell Synchronizationmentioning
confidence: 99%
“…In liver cancer, the phosphorylation of AKT is remarkably intensified; therefore, AKT has become an important target of anti-cancer research (Yap et al, 2008). Studies on breast cancer and prostate cancer suggested that PI3K/AKT could increase the expression of S-phase kinase-associated protein 2 (Skp2) at different levels, transcription, translation, and post-translation, to promote the occurrence of tumors (Gao et al, 2009;Lin et al, 2009;Li et al, 2013). In this study, the expression of PI3K and AKT in colorectal cancer was significantly higher than those in tumor-adjacent tissues, and was closely correlated with the differentiation level of colorectal cancer ( Li et al.…”
Section: Discussionmentioning
confidence: 99%
“…One of the most significant extensions to our understanding of isoform-specific Akt signaling was the identification of Skp2 as a direct target of Akt1 (33,34). The Akt1-mediated phosphorylation of Skp2, a component of the SCF complex E3 ligase, ensures cell cycle progression by degradation of p27, a potent inhibitor of Cdks.…”
Section: Isoform-specific Signaling To Downstream Substratesmentioning
confidence: 99%